Seismic wave characteristics in anisotropic attenuating media . - Sinha, Satish. (My University, 2006)
Seismic anisotropy in shales is a complex phenomenon. A number of theoretical shale models are investigated to study the effects of clay orientation, aspect ratio of cracks, porosity and fluid types on the synthetic seismograms.

A synthetic seismogram is a tool to investigate seismic wave characteristics in anisotropic attenuating media. A numerical technique for the computation of synthetic seismograms in a homogeneous, as well as in a multilayered anisotropic medium was developed. Full waveform theory is used to compute the synthetic seismograms. The medium can be elastic or viscoelastic. In the latter case, attenuation is introduced by giving materials complex elastic constants. To ensure that there are no false arrivals in the synthetic seismogram, it is important to carefully control the integration kernel singularity points, especially those due to repeated roots of the associated Green-Christoffel equation. A novel approach is developed to safely track the continuity of the integration kernel and, hence, the polarization vectors in critical and supercritical zones.

The reflectivity approach is followed to consider wave propagation in a multilayered medium. A simple and concise implementation of this method is developed. This approach also enables one to investigate frequency dependent reflection coefficients varying with incidence angle and azimuth. The modeling of reflection coefficients in fractured media suggests that amplitude versus offset and azimuth (AVOAz) can be helpful in detecting fractured reservoirs.

In a new development, the effect of attenuation on P- and S-wave radiation patterns in viscoelastic anisotropic media is investigated. The understanding of radiation patterns in homogeneous media is applied to interpret various wave types in attenuating multilayered media. Both the amplitude and the frequency content of the synthetic seismograms are affected by attenuation properties of the media. The spectral decomposition technique is found to be useful in our understanding of the attenuation effects.
Keywords: Wave equation.; Seismic prospecting.; Shale.; Geophysics.; Seismograms.